Process and Pharmacological Potentials of Kasisa bhasma, a Herbo-Mineral Formulation with Calcinated Ferrous Sulphate - Raju, Prasanna; Rasheed, Arun; Basha, Jamal; M, Anvesh; AK, Azeem (Jordan Journal of Pharmaceutical Sciences, 2016)
Objective: To process, standardize and assess the Kasisa bhasma formulation.Methods: The Kasisa bhasma (AK1) was processed in strict accordance to Ayurvedic formulary of India. AK1was characterized physicochemically by FT-IR, TGA, SEM, AFM, XRD and AAS techniques. Formulation wasassessed for anti-anemic, hepatoprotective and toxicity potentials using albino rats. The commercially marketedKasisa bhsma (AK2) formulation was also used for comparative study.Results: The FT-IR spectra showing principal inorganic, hydrated metal salt or oxide peak was an indicative ofbhasma. The XRD analysis of both formulations exhibited crystalline nature and nano-sized particles whendetermined using Scherrer formula. SEM showed well-defined plate like structures of ferric oxide in AK2 whileAK1 showed spongy, relatively compact microcrystalline aggregates with loss of grain boundaries. AFManalysis confirmed the spherical morphology of AK1 and AK2 due to aggregation of nanocrystals of metallicoxides in the formulation. The presence of ferric oxide in nano-crystalline size was confirmed by TGA curvesand quality by AAS study. The formulations AK1 and AK2 had exhibited anti-anemic and hepatoprotectivepotentials in albino rats. No toxicity was reported in histopathological study.Conclusion: The schematic process of Kasisa bhasma imparts quality in the formulation and standardizationprotocols and may therefore be considered as a fingerprinting of Kasisa bhasma using sophisticated analyticaltechniques.